Vjacheslav Sergijovych Dudnik - "ORTHOPAEDICS, TRAUMATOLOGY; PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
On May 13, 2021, at the age of 75, the heart of the scientist, orthopedist-traumatologist, candidate of medical sciences Dudnik Vyacheslav Sergeevich stopped beating.